An Analysis of Ethnomathematics Didactical Contract in the Sums of Interior and Exterior Angles - Ali, Clement Ayarebilla (S&Co Publishing, 2024)
Teachers and students have different ideas and expectations about the didactical situation that evolves in the classroom. It needs rules that determine teachers’ and students’ unique responsibilities relating to the didactical situation or contract. The division of roles and responsibilities moves from the teacher as the centre to the students as the centre. The results of a case study design of 42 students showed that the transition from ostentation to Mayeutic Socrate and then to the adidactical contracts was smooth and progressive if the teacher and the participants cooperated and actively participated in the milieu. It was therefore recommended that teachers streamline method-friendly guidelines, strategies, and techniques at the ostentation contract for students to emulate, students cooperate and support the teacher at the mayeutic Socratic contract and the knowledge of both local indigenous and exotic artifacts must complement each other at the adidactical contract.